Peran Mahasiswa Prodi TBI Dalam Penguatan Materi Self-Introduction Bagi Siswa Sekolah Dasar DI Kota Palangka Raya - Alya Audria; Zaitun Qamariah; Akhmad Ali Mirza (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
This community service activity involves a collaboration between lecturers and students of the English Education Program (Tadris Bahasa Inggris - TBI) to strengthen the self-introduction skills of fourth-grade students at MI Hidayatul Insan, Kota Palangka Raya. Through interactive and enjoyable learning methods, students actively serve as facilitators and mentors, helping students develop their English skills. The activities include introductory sessions, repeated practice, and educational games designed to boost students' confidence in introducing themselves. The results show a significant improvement in students' ability to perform self-introductions smoothly and confidently. This collaborative approach not only provides immediate benefits to the students but also enriches the teaching experience of the TBI students, preparing them to become more competent educators. In conclusion, the involvement of TBI students in strengthening self-introduction materials effectively enhances the English language skills of elementary school students.